Collaborative design of accessible information with people with aphasia. Issue 12 (2nd December 2019) - Herbert, Ruth; Gregory, Emma; Haw, Caroline
ABSTRACT: Background : People with aphasia report preferences for specially formatted health information materials, but there is little evidence that modified materials result in improved comprehension. Potential explanations for this include language included not taking account of aphasic processing difficulties, topics unrelated to aphasia, lack of clarity regarding the use of images, and the lack of end-user involvement in the design. Additionally, no definitive criteria for production of accessible information have been identified. Aims : The first aim of this study was to collaborate with people with aphasia in an iterative design process to develop and finalise accessible information materials. The second aim was to identify definitive criteria for use in the future production of information materials for people with aphasia. Methods and procedure : Prototype materials were developed for the study, based on criteria identified from the existing research into aphasia-accessible information, and on the evidence base concerning language processing in aphasia. Fourteen people with aphasia took part in two rounds of consensus group meetings and viewed information about aphasia presented within the prototype materials. Consensus points were identified within the groups through discussion and through ratings using Likert scales. The set of consensus points and ratings were adapted into criteria for graphic designers to incorporate into subsequent designs of the materials, in order to generate a final version, and related criteria. Outcomes and results : The group discussions and the ratings of materials led to the identification of an agreed layout within which to present information, and specific criteria for the following: information consisting of one proposition expressed via everyday words and canonical syntactic forms; one or two images relating directly to keywords; sans serif typography with keyword emphasis. Individual preferences with regard to image types were identified. Novel criteria were identified in the study, relating to layout, language, images and typography. These were added to the original set of criteria to form definitive criteria for use in the development of accessible aphasia materials. Conclusions : This study successfully involved people with aphasia in the design process to produce novel materials, and related design criteria. The resulting materials and criteria differ from those previously proposed, by reflecting directly people with aphasia's views and preferences, and by incorporating language and images suitable for people with aphasia, based on the existing research evidence and the outcomes of this study. The materials and criteria have the potential to improve people with aphasia's understanding of health information.